Changes of Built-Up and Related Areas in Slovenia - Žiberna, Igor; Ivajnšič, Danijel; Konečnik Kotnik, Eva (Journal for Geography, 2023)
This research analyses changes of built-up and related areas in Slovenia in the period 2000-2023. Results are prepared on the level of statistical regions and municipalities. Special emphasis is orientated towards original categories of land use, on which built-up and related areas are located today. Finally, we discuss the expansion of built-up and related areas into arable areas, especially those that are extremely important for agriculture and food production.